Modification of gold electrode with a monolayer of self-assembled microgels. (1st April 2018) - Mackiewicz, Marcin; Marcisz, Kamil; Strawski, Marcin; Romanski, Jan; Stojek, Zbigniew; Karbarz, Marcin
Abstract: A new method of modification of the gold-electrode surface with a microgel monolayer was developed. Microgel particles contained –S-S– groups to enable modification of the gold surface by self-assembly via the chemisorption process. The particles were obtained by precipitation polymerization of N -isopropylacrylamide with N, N ′-bis(acryloyl)cystine cross-linker. Their spherical shape and highly uniform dispersion were confirmed by electron microscopies (SEM and TEM). Thermosensitivity of the microgel was investigated with dynamic light scattering (DLS). The formation of monolayers was monitored with a quartz-crystal microbalance. The morphology of the modified surface in its dry state and in aqueous environment was investigated with atomic force microscopy (AFM). At temperatures below the volume-phase-transition temperature the microgels formed a densely packed structure that well covered the entire surface. A significant change in morphology was observed after raising temperature above the volume-phase-transition temperature. The observed increase in roughness of the modified surface suggested that the surface of electrode could be locally, between the microgel particles, uncovered. The electrochemical properties of the modified electrode were investigated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). A strong influence of the volume phase transition in the microgels attached to the Au surface on CV and EIS responses of the modified electrode was found. The observed behavior was reversed to that of the electrodes modified with a thin thermosensitive gel film based on N-isopropylacrylamide, i.e. the volume phase transition led to a significant increase in the voltammetric current and to a drop in electron transfer resistance. That was related to partial uncovering of the electrode surface after the shrinking process in the microgels.